2021
DOI: 10.3390/microorganisms9081719
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Syndrome: Nine Months after SARS-CoV-2 Infection in a Cohort of 354 Patients: Data from the First Wave of COVID-19 in Nord Franche-Comté Hospital, France

Abstract: (1) Background. Post-COVID-19 syndrome is defined as the persistence of symptoms after confirmed SARS-CoV-2 infection. (2) Methods. ANOSVID is an observational retrospective study in Nord Franche-Comté Hospital in France that included adult COVID-19 patients confirmed by RT-PCR from 1 March 2020 to 31 May 2020. The aim was to describe patients with post-COVID-19 syndrome with persistent symptoms (PS group) and to compare them with the patients without persistent symptoms (no-PS group). (3) Results. Of the 354 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 30 publications
4
48
0
2
Order By: Relevance
“…In our study, HCWs were more represented in the R group. ANOSVID, another study conducted in our institution [51], found similar results and suggested that recrudescent or persistent symptoms could be favored by post-traumatic stress or due to stress generated by the responsibility of care in the epidemic context. However, there is currently no description in the literature of specific clinical or demographic characteristics that could predict the resurgence of symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…In our study, HCWs were more represented in the R group. ANOSVID, another study conducted in our institution [51], found similar results and suggested that recrudescent or persistent symptoms could be favored by post-traumatic stress or due to stress generated by the responsibility of care in the epidemic context. However, there is currently no description in the literature of specific clinical or demographic characteristics that could predict the resurgence of symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, the prevalence of symptoms that remain 12 weeks after SARS-CoV-2 infection in patients non-hospitalized may be as small as 3.0%, based on tracking specific symptoms (tighter definition), to 11.7% based on the wider questionnaire which includes the questions about the 21-symptom list that was recently reported from 26,922 UK residents by The Office for National Statistics [15]. Numerous studies report intermediate prevalence rates between the above-mentioned ones [16,17]. The results clearly indicate that age, being female, poor general health, pre-existing health conditions, high viral load, obesity or being overweight and white ethnicity were associated with higher risk of long COVID in the majority of the studies [7,11,12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the demographic composition and clinical presentation of long-COVID patients in the current study was comparable to other reports on long-COVID. [20][21][22] Several previous studies on long-COVID were conducted before the availability of specific diagnosis codes for long-COVID or before outpatient clinics were established to manage these complex patients. 8,23 Moreover, most studies have been based on clinical cohorts with inherent limitations in sample size and followup.…”
Section: Discussionmentioning
confidence: 99%
“…8,23 Moreover, most studies have been based on clinical cohorts with inherent limitations in sample size and followup. [4][5][6]21,22 These combined considerations highlight the need for additional registry-based research using specific and validated diagnosis codes in large population-based cohorts of previously hospitalized and nonhospitalized COVID-19 patients with matched control groups in order to learn more about long-COVID and the potential consequences of the disease.…”
Section: Discussionmentioning
confidence: 99%